2020
DOI: 10.1038/s41598-020-79495-5
|View full text |Cite
|
Sign up to set email alerts
|

CT fatty muscle fraction as a new parameter for muscle quality assessment predicts outcome in venovenous extracorporeal membrane oxygenation

Abstract: Impaired skeletal muscle quality is a major risk factor for adverse outcomes in acute respiratory failure. However, conventional methods for skeletal muscle assessment are inapplicable in the critical care setting. This study aimed to determine the prognostic value of computed tomography (CT) fatty muscle fraction (FMF) as a biomarker of muscle quality in patients undergoing extracorporeal membrane oxygenation (ECMO). To calculate FMF, paraspinal skeletal muscle area was obtained from clinical CT and separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Thereby, FMF was recently proposed as an easy-accessible body composition metric which may be considered particularly promising as it additionally integrates information on skeletal muscle quality [1,5]. Previous studies have demonstrated its prognostic value both as an indicator of frailty in patients with planned endovascular aortic valve replacement as well as an powerful predictor of outcome in critically ill patients receiving extracorporeal membrane oxygenation therapy [1,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, FMF was recently proposed as an easy-accessible body composition metric which may be considered particularly promising as it additionally integrates information on skeletal muscle quality [1,5]. Previous studies have demonstrated its prognostic value both as an indicator of frailty in patients with planned endovascular aortic valve replacement as well as an powerful predictor of outcome in critically ill patients receiving extracorporeal membrane oxygenation therapy [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…In the second part, the extracted 2D image is segmented into three compartment classes: visceral and subcutaneous adipose tissue (VAT, SAT) and skeletal muscle (SM). The fatty muscle fraction (FMF), a quantitative marker for fatty muscle degeneration, is determined in a subsequent post-processing step [1,6]. For both deeplearning-based slice extraction and segmentation, classical machine learning methods were employed for integration of quality control steps that capture the predictive uncertainty during deployment.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by Bear DE et al, the initial condition of the skeletal muscle index of patients with ARDS was related to the duration of VV ECMO, and most specifically, low skeletal muscle index resulted in longer VV ECMO duration, while preserved initial skeletal muscle index was associated with better survival [36]. Finally, fatty muscle fraction through CT imaging seems to be a predicting biomarker of 1-year mortality and a promising muscle quality imaging biomarker in ECMO patients [37].…”
Section: Prevalence and Risk Factors Of Icu-awmentioning
confidence: 99%
“…Skeletal muscle quality is an established target and determinant of functional recovery and thereby outcome in patients with acute severe illness [ 5 ]. Fatty infiltration of skeletal muscle, also called myosteatosis, is a progressive multifactorial skeletal muscle affection, which is commonly associated with aging and obesity and is known to increase the risk of adverse clinical outcomes and physical disability in many pathologies [ 5 11 ].…”
Section: Introductionmentioning
confidence: 99%